HIV care continuum interventions for Black men who have sex with men in the USA. Issue 12 (December 2021) - Goldhammer, Hilary; Mayer, Kenneth H; Marc, Linda G; Psihopaidas, Demetrios; Chavis, Nicole S; Massaquoi, Massah; Cahill, Sean; Downes, Alicia; Koester, Kimberly; Fields, Sheldon D; Cohen, Stacy M; Keuroghlian, Alex S
Summary: Disparities persist along the HIV care continuum among Black men who have sex with men (MSM) in the USA. As part of an initiative funded by the Health Resources and Services Administration's HIV/AIDS Bureau (US Department of Health and Human Services), we searched for recently published interventions focused on improving HIV care continuum outcomes among Black MSM with HIV in the USA. Our search identified 14 interventions, all of which were associated with at least one statistically significant outcome. Medication adherence was the most common outcome of interest, and linkage to care was the least common. More than half of the interventions focused on younger populations and took place in the US South. Interventions used a range of strategies to increase cultural relevance and address common barriers to optimal HIV outcomes for Black MSM. Several interventions harnessed social media, text messaging, and smartphone apps to facilitate social support, deliver HIV education, and encourage medication adherence. Interventions were delivered mostly at the individual or interpersonal level, although three made system-level changes to address structural barriers. Notably missing were interventions focused on minimising behavioural health barriers, and interventions directly addressing social determinants of health such as housing. To accelerate the pace of implementation and scale-up of interventions for Black MSM with HIV, public health entities can pilot emerging interventions in real-world settings, and use an implementation science approach to evaluate outcomes and assess the implementation strategies that drive or hinder effectiveness.